2007
DOI: 10.4028/www.scientific.net/msf.539-543.4720
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of Cementite in High Strength Steel Plates by Rapid Heating and Tempering

Abstract: The precipitation behavior of cementite in low carbon steels at various heating rates from 0.3 to 100 K/s has been studied using a high-frequency induction heating apparatus. The materials used in this study were steel platesfor welded structures: 610 and 780 MPa class steel plates with a mixed microstructure of bainite and martensite.Cementite was observed using a carbon extraction replica method and the hardness and toughness were also examined. When heated at the conventional slow rate of 0.3 K/s, relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…[24,25] Corroborating the present work, Furuhara et al also reported difference in locations of cementite precipitation in nonisothermal and isothermal tempering at 923 K (650°C). [24] In nonisothermal tempering, finer cementite precipitated within laths and interlath regions compared to that at prior-c and block boundaries, whereas isothermal holding (3600 seconds) resulted in growth of the cementite at all locations, but the trend in cementite size at location remained similar.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…[24,25] Corroborating the present work, Furuhara et al also reported difference in locations of cementite precipitation in nonisothermal and isothermal tempering at 923 K (650°C). [24] In nonisothermal tempering, finer cementite precipitated within laths and interlath regions compared to that at prior-c and block boundaries, whereas isothermal holding (3600 seconds) resulted in growth of the cementite at all locations, but the trend in cementite size at location remained similar.…”
Section: Resultssupporting
confidence: 62%
“…This may be because DP M steel has lean chemistry, whereas the steel of Furuhara et al [24] has high carbon and Cr content, which restricts growth of the cementite in tempering. [25] From the aforementioned locations and size of cementite in both the tempered structures of DP M steel, it was concluded that precipitation of cementite is controlled by diffusion of carbon atoms to lattice defects in the following order: prior-c grain boundaries and block boundaries (larger cementite), lath boundaries (fine interlath cementite), and dislocations (finer intralath cementite). This finding is very consistent with earlier reports on isothermal tempering of low-carbon martensite describing cementite precipitation in the early stages of tempering and its consequent coarsening at the same locations by increasing temperature.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Nagao et al 21) reported that the main nucleation site of cementite shifts from lath boundary to within lath during the heating process of tempering. The dislocation density is greatly increased after quenching, especially in the steels subjected to ausforming.…”
Section: Microstructures and Mechanical Propertiesmentioning
confidence: 99%